2001
DOI: 10.1006/jmla.2000.2742
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Geometry and Function in the Comprehension of Over, Under, Above, and Below

Abstract: Three experiments are reported which examined the role of geometry and functional relations in the comprehension of the spatial prepositions over, under, above, and below. The tasks used consisted of rating how appropriate sentences (containing one of these prepositions) were to describe a series of pictures. For example, the pictures comprised a person holding an object with the function of protection from falling objects (e.g., an umbrella). Each picture was depicted with the object shown as fulfilling its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 21 publications
7
97
0
5
Order By: Relevance
“…Our findings have implications for studies in which the orientation of the LO is manipulated to investigate this aspect (e.g., Carlson-Radvansky & Radvansky, 1996;Coventry et al, 2001). According to our results, the orientation of the LO affects spatial language apprehension even when no functional relationship links the LO and the RO.…”
Section: Spatial Language Perception and Actionmentioning
confidence: 81%
“…Our findings have implications for studies in which the orientation of the LO is manipulated to investigate this aspect (e.g., Carlson-Radvansky & Radvansky, 1996;Coventry et al, 2001). According to our results, the orientation of the LO affects spatial language apprehension even when no functional relationship links the LO and the RO.…”
Section: Spatial Language Perception and Actionmentioning
confidence: 81%
“…Additionally, the uses of angular terms are all influenced by the contextual/functional information. For instance, Coventry and his colleagues (Coventry et al 2001) manipulated the scenes, which depict the relations such as 'under', 'over', 'above', 'below', and asked his participants to make acceptability judgments with respect to a given preposition in English. The results indicated that the participants made judgments according to the function of the objects in the scenes regardless of the objects' positionings with respect to the human figure.…”
Section: Recent Findings On the Spoken Language Expressions On Angulamentioning
confidence: 99%
“…Finally, we note that the meanings of spatial relational terms incorporate nonspatial factors such as support and containment relations, intended function, and so on (Bowerman & Pederson, 1992;Coventry & Garrod, 2004;Coventry, Prat-Sala, & Richards, 2001;Feist, 2000Feist, , 2004Feist & Gentner, 2003;Talmy, 1988;Vandeloise, 1991), in addition to geometry. Given that spatial meaning is in fact quite complex, a question for further research is how these factors interact with geometric factors in the encoding of spatial scenes.…”
Section: Extended Effectsmentioning
confidence: 99%